Analysis of workload, career development, and compensation for employee retention at PT Angkasa Pura Indonesia - Anas Sobirin; Dwi Dewianawati; Anis Sirojuddin Suryo Negor (Institute of Computer Science (IOCS), 2025)
In the workplace, especially companies, they must have good human resource management. One of them is related to fulfilling what employees need or the rights of the employees themselves based on the regulations and agreements that have been agreed upon by both parties. Therefore, in this case, the company will not lose employees, especially those who have great potential for the company. This study aims to analyze the influence of workload, career development, and work compensation on employee retention at PT Angkasa Pura Indonesia (Case Study at Zainuddin Abdul Madjid International Airport Lombok). The method used was quantitative by distributing questionnaires to 108 non-structural permanent employees. Data were analyzed using validity tests, reliability tests, classical assumption tests, regression analysis, hypothesis testing, and determination coefficients. The results show that these three independent variables have a positive and significant effect on employee retention, either partially or simultaneously, with career development having a dominant effect